Interaction of Corrosion-Cumulative Fatigue and Shot Peening of 1100-H12 Aluminum Alloy - Alalkawi, H .J.M; Maajeed, Amer Hameed; Betti, Zainab Azeez (Al-Khwarizmi Engineering Journal, 2015)
Abstract    Corrosion-fatigue occurs by the combined actions of cyclic loading and corrosive environment. The effect of shot peening on cumulative corrosion-fatigue life of 1100-H12 Al alloy was investigated. Before fatigue testing, specimens were submerged in 3.5%NaCl solution for 71 days. Constant fatigue tests were performed with and without corrosive environment. Cumulative corrosion-fatigue tests were also carried out in order to determine the fatigue life before and after shot peening. The constant fatigue life was significantly reduced due to corrosive environment and the endurance fatigue limit was reduced by 13% compared with dry fatigue. In case of shot peening the cumulative , corrosion -fatigue life was increased by a factor of about (2) compared with cumulative corrosion-fatigue life without shot peening.It was found that the CFLIF%(Cumulative Fatigue Life Improvement Factor) was about (2-6) due to shot peening surface treatment .Keywords: Corrosion -fatigue , shot peening , 1100-H12 Al alloy, cumulative fatigue damage.